Enhancing energy efficiency of oil and petrochemical industries - Baskaran, Ramalingam (2012)
Oil and petrochemical industry is composed of many different unit processes and unit operations. As this type of industries spends typically 50% of cash operating costs (i.e.,, excluding capital costs and depreciation) on energy, making energy a major cost factor and also an important opportunity for cost reduction. Energy use is also a major source of emissions in the refinery industry making energy efficiency improvement an attractive opportunity to reduce emissions and operating costs.